Asimetri Informasi dalam Holding Period Saham: Sebuah Kajian Literatur Sistematis - Fonna, Rizki Putri Nurita; Adnan, Muhammad Ichsan; Fajri, Abdul Malik (Akbis: Media Riset Akuntansi dan Bisnis, 2025)
This paper is designed to systematically investigate the influence of information asymmetry on stock holding periods using a Systematic Literature Review (SLR) approach. The literature was gathered through the Publish or Perish software, utilizing data from the Google Scholar database for 2020–2025 with the keywords “Holding Period” and “Stock.” From an initial search that yielded 77 articles, 21 were selected based on criteria related to research focus, methodology, and accessibility. These selected articles were further analyzed to identify research trends, methodological approaches, key variables, and contexts. The findings indicate that information asymmetry, frequently assessed through the bid-ask spread, it has a substantial impact on investors’ decision-making regarding the duration of stock ownership. Although the literature presents some variation in findings, most evidence suggests that higher levels of information asymmetry tend to shorten holding periods due to increased uncertainty and risk. The review also highlights that most publications on this topic originate from Universitas Pelita Bangsa. The study enhances the body of literature in this field by consolidating scattered evidence and presenting a comprehensive review, while identifying future research directions in behavioral finance and market transparency.